Chiral‐selective etching effects on carbon nanotube growth at edge carbon atoms. Issue 2 (12th December 2018) - Kimura, Ryuto; Hijikata, Yuh; Eveleens, Clothilde A.; Page, Alister J.; Irle, Stephan
Abstract : Chemical vapor deposition (CVD) utilizing metal cluster nanoparticle catalysts is commonly used to synthesize carbon nanotubes (CNT), with oxygen‐containing species such as water or alcohol included in the feedstock for enhanced yield. However, the etching effect of these additives on the growth mechanism has rarely been investigated, despite evidence suggesting that etching potentially affects the chirality distribution of product CNTs. We used quantum chemical methods to study how water‐based etchant radicals (OH and H) may enhance the chiral selectivity during CVD growth using CNT cap models. Chemical reactivities of the caps with the etchant radicals were evaluated using density functional theory (DFT). It was found that the reactivities on the cap edges correlate with the chirality of the caps. These results suggest that proper selection of etchant species can provide opportunities for selective chirality control of the product CNTs. © 2018 Wiley Periodicals, Inc. Abstract : Achievement of carbon nanotube (CNT) growth with pure chirality is indispensable for practical usage, while etching effects of reactive species are often looked over in the CNT growth process. The reactivities of etchant and growth species on the edges of carbon nano cap models suggest that balance of the reactivities is an important factor for the chiral selectivity of CNT growth, namely, proper selection of those species can provide chiral‐selective CNTs.